Making Work Pay for the Indebted: The Effect of Debt Services on the Exit Rates of Unemployed Individuals - Pierre Koning (Institute for the Study of Labor (IZA), 2013)
This paper investigates the effectiveness of an intervention that was targeted at a specific group of Dutch Social Assistance (SA) recipients with debt problems. With a large share of the income gains of work resumption were transferred to the creditors, these individuals experienced a strong a priori disincentive to resume formal work. The direct aims of this intervention were therefore twofold: the restructuring of personal debts and the prevention of new debt problems to arise. We use the timing-of-events method to identify the effects of debt programs on SA spells. Our key finding is that the provision of debt services substantially increased the exit out of the SA schemes, but this was mainly due to exits out of the labor force. This suggests individuals perceived or experienced program as unpleasant and opted to exit without work. At the same time, the debts program offer increased the exit rate for targeted individuals that did not show up, probably due to increased monitoring and sanction activities.
Keywords: C21; D14; H75; I38; J18; K35; 330; debt services; program evaluation; threat effects